Public finance and demography - Shakirova, Alsu; Vítek, Leoš, 1970-; Arltová, Markéta, 1970-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis focuses on the impact of reproductive behaviour on fiscal sustainability in developed and developing countries during the period from 1990 to 2020. The theoretical part reviews the first and second demographic transitions, the U-shaped curve of female labor force participation, the concept of fiscal sustainability, and current trends in the main indicators across different countries. The practical part analyzes the data, explains the methods used, and compares the results for developed and developing countries. Panel data models and the Autoregressive Distributed Lag model are used for the analysis, which was conducted using the software EViews. The findings show that female labor force participation and fertility help reduce debt levels and improve fiscal sustainability in developed countries. In developing countries, however, reproductive behaviour indicators have a negative impact on fiscal sustainability. Other demographic and economic factors, however, have a stronger effect on debt levels.
Vedoucí práce: Leoš Vítek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses